EMERGING ISSUES IN POST-BREXIT BRITAIN AND NIGERIA RELATIONS - Abraham Ejogba, ORHERO,; Henry Ejotubo, OGBE, (International Journal of Psychosocial Rehabilitation, 2024)
In recent Times, President Muhammadu Buhari and a great lot of Nigerian people, especially Nigerians in the Diaspora alike hoped for golden times of rediscovered but deeper and partnerlike post-Brexit relations. Nigerians in diaspora considered Brexit as an opportunity for Nigeria to harness human capital development in Britain. it is open to question what UK could offer which other competitors such as USA, Russia, France, China and India do not have already on their agenda. Brexit favours economic nationalism, mercantilist doctrines of protectionism and an emphasis on national interest over international interest. It has consequences which suggest a resurgence of political realism; this is contrary to the liberal undertones of the European Union. It is against this backdrop that this paper addresses emerging issues in post-Brexit Britain and Nigeria relations. The paper adopted qualitative research design as data were collected from secondary sources. The technique of content analysis was applied to analyze the data collected which helped us to make interpretations coherently. This paper adopted the contagion effect theory as theoretical framework of analysis. The paper concludes that Brexit decision is fraught with political, economic, immigration and security implications that would spread far beyond its borders. The paper therefore recommends among others that Nigerian government should ensure mutual interest in the post-Brexit trade relations to be negotiated and a more liberal attitude on all fronts is required to promote progressive trade partnership between Nigeria and Britain.